Feedback between sediment and light for seagrass: Where is it important?. (24th June 2016) - Adams, Matthew P.; Hovey, Renae K.; Hipsey, Matthew R.; Bruce, Louise C.; Ghisalberti, Marco; Lowe, Ryan J.; Gruber, Renee K.; Ruiz‐Montoya, Leonardo; Maxwell, Paul S.; Callaghan, David P.; Kendrick, Gary A.; O'Brien, Katherine R.
Abstract: A feedback between seagrass presence, suspended sediment and benthic light can induce bistability between two ecosystem states: one where the presence of seagrass reduces suspended sediment concentrations to increase benthic light availability thereby favoring growth, and another where seagrass absence increases turbidity thereby reducing growth. This literature review identifies (1) how the environmental and seagrass meadow characteristics influence the strength and direction (stabilizing or destabilizing) of the seagrass‐sediment‐light feedback, and (2) how this feedback has been incorporated in ecosystem models proposed to support environmental decision making. Large, dense seagrass meadows in shallow subtidal, non‐eutrophic systems, growing in sediments of mixed grain size and subject to higher velocity flows, have the greatest potential to generate bistability via the seagrass‐sediment‐light feedback. Conversely, seagrass meadows of low density, area and height can enhance turbulent flows that interact with the seabed, causing water clarity to decline. Using a published field experiment as a case study, we show that the seagrass‐sediment‐light feedback can induce bistability only if the suspended sediment has sufficient light attenuation properties. The seagrass‐sediment‐light feedback has been considered in very few ecosystem models. These models have the potential to identify areas where bistability occurs, which is information that can assist in spatial prioritization of conservation and restoration efforts. In areas where seagrass is present and bistability is predicted, recovery may be difficult once this seagrass is lost. Conversely, bare areas where seagrass presence is predicted (without bistability) may be better targets for seagrass restoration than bare areas where bistability is predicted.